The Gap Between Farm Price and Sale Price of the Fluid Milk Industry in Sri Lanka - Herath, H. M. R. P. (Journal of Commerce and Trade, 2016)
Sri Lanka has a potential of producing substantial amount of high quality milk but the issues and obstacles currently the milk industry is facing obstruct the production to its maximum capacity causing a huge gap between the farm gate price and sale price. Powdered milk is cheaper than fluid milk and is sourced from the international market. This is also a barrier,fluid milk industry to develop, although it has a considerable impact on the Sri Lankan economy inproviding job opportunities. It is also important as a source of alleviating nutritional poverty in all age groups. And it is a source of extensive employment opportunities. Therefore this researchis focused to identify the factors affecting to create a gap between farm gate price and shelf price of fluid milk and qualitative approach was used to achieve the research objectives.A simple thematic analysis was carried out to identify the barriers that create a huge gap between farm gate price and selling price of fluid milk. The required primary data were gathered through key informant interviews and secondary data through available literature on dairy industry. Thematic analysis was based on both secondary and primary data. Issues in milk processing and production Issues in distribution channels (High cost involving with transport, the lack of technology development and infra-structure facilities, the lack of sufficient yield, poor veterinary services and high production cost are the factors that create a huge gap between farm gate price and sale price of fluid milk in Sri Lanka.